Perbandingan Perlindungan Hukum Merek antara Prinsip First to File Hukum Indonesia dan Prinsip First to Use pada Hukum Australia - Neisa Ines Tritanaya; Wiwin Yulianingsih (Yustisia Tirtayasa, 2022)
Intellectual Property Rights are the exclusive rights to do something on the intellectual property, which is regulated by the norms or applicable laws. This study aims to determine the difference between the first to file principle in Indonesian law and the first to use principle in Australian law and to determine the strengths and weaknesses between the two principles. Indonesia adheres to a â€œfirst to fileâ€ system, which requires a trademark to be registered to obtain legal protection. While "first to use" is a brand protection system that recognizes unregistered/unregistered marks used as trademarks. This study uses a normative juridical research method with data sources obtained from literature studies consisting of primary legal materials, secondary legal materials and tertiary legal materials derived from interviews, books, scientific journals, and legislation, then analyzed using the method descriptive analysis. The results of the study indicate that there are several differences regarding the regulation of trademarks that have not been regulated in Indonesian law but are regulated in Australian law. The principles adopted by Indonesia are easier to prove in the event of a dispute compared to the principles adopted by Australia